DrugSpaceX: a large screenable and synthetically tractable database extending drug space. Issue Volume 49:Issue D1(2021) (26th October 2020) - Yang, Tianbiao; Li, Zhaojun; Chen, Yingjia; Feng, Dan; Wang, Guangchao; Fu, Zunyun; Ding, Xiaoyu; Tan, Xiaoqin; Zhao, Jihui; Luo, Xiaomin; Chen, Kaixian; Jiang, Hualiang; et al.
Abstract: One of the most prominent topics in drug discovery is efficient exploration of the vast drug-like chemical space to find synthesizable and novel chemical structures with desired biological properties. To address this challenge, we created the DrugSpaceX (https://drugspacex.simm.ac.cn/ ) database based on expert-defined transformations of approved drug molecules. The current version of DrugSpaceX contains >100 million transformed chemical products for virtual screening, with outstanding characteristics in terms of structural novelty, diversity and large three-dimensional chemical space coverage. To illustrate its practical application in drug discovery, we used a case study of discoidin domain receptor 1 (DDR1), a kinase target implicated in fibrosis and other diseases, to show DrugSpaceX performing a quick search of initial hit compounds. Additionally, for ligand identification and optimization purposes, DrugSpaceX also provides several subsets for download, including a 10% diversity subset, an extended drug-like subset, a drug-like subset, a lead-like subset, and a fragment-like subset. In addition to chemical properties and transformation instructions, DrugSpaceX can locate the position of transformation, which will enable medicinal chemists to easily integrate strategy planning and protection design.